Herbal Frontiers: The Role of Alternative Remedies in Combating Typhoid Fevers - Mohd. Wasiullah; Piyush Yadav; Shashikant Maury; KishanKumar (Recent Trends in Infectious Diseases, 2025)
Typhoid fever, caused by Salmonella typhi, remains a major health challenge, particularly in developing regions where sanitation and healthcare resources are limited. With an estimated global incidence of 17 million cases annually, the disease poses a significant public health burden. The growing resistance to conventional antibiotics, such as fluoroquinolones and third-generation cephalosporins, exacerbates treatment challenges. This has spurred interest in alternative remedies, including herbal and homeopathic treatments.Herbal medicine offers a wealth of bioactive compounds that have antimicrobial, anti-inflammatory, and immune- boosting properties. Commonly used herbs like Giloy (Tinospora cordifolia), Tulsi (Ocimum sanctum), and Jatamansi (Nardostachys jatamansi) demonstrate efficacy in reducing fever, enhancing immunity, and alleviating gastrointestinal symptoms. These plants are widely accessible, affordable, and culturally accepted in many regions, making them a valuable resource for combating typhoid fever. Additionally, combinations of plant-derived compounds with antibiotics have shown synergistic effects, potentially reversing bacterial resistance.Homeopathy, rooted in individualized treatment and the principle of "like cures like," provides another alternative approach. Remedies such as Baptisia tinctoria and Belladonna are explored for their targeted applications in managing typhoid symptoms, including fever, systemic inflammation, and digestive disturbances. Despite its growing acceptance, scientific validation of homeopathy remains limited, necessitating further research.This review highlights the potential of integrating alternative medicine into modern healthcare to address the limitations of conventional treatments. Rigorous clinical trials are essential to establish safety, efficacy, and dosage, paving the way for innovative, holistic strategies to combat typhoid fever. Keywords: Salmonella typhi, herbal medicine, homeopathy, antimicrobial resistance, alternative therapies.
Keywords: Bioactive; Homeopathy; MDR; Medicinal Plants; Salmonella typhi; Typhoid